Expression of interleukin 1, interleukin 27, and TNF α genes in patients with ischemic cardiomyopathy versus idiopathic dilated cardiomyopathy: A case‐control study. Issue 4 (26th June 2022) - Iravani Saadi, Mahdiyar; Salami, Javad; Abdi, Hanieh; Kheradmand, Nadiya; Nabi Bdolyousefi, Ehsan; Torkamani, Mahmoud; Karimi, Zahed; Agah, Shahram; Rahimian, Zahra; Manafi, Alireza
Abstract: Background and Aims: Congestive heart failure is a complex multifactorial syndrome due to tissue hypoperfusion that is affected by some factors like inflammatory cytokines. In our study, we investigated the exact gene expression of three inflammatory cytokines in ischemic and idiopathic cardiomyopathy patients. Methods: From 49 studied recipients in the ischemic group, 23 (46.9%) were male and from 40 studied recipients in the idiopathic dilated cardiomyopathy group, 19 (47.5%) were male. For the quantitative analysis of interleukin (IL)‐1, IL‐27, and tumor necrosis factor (TNF)‐α messenger RNAs expression level, the SYBR Green real‐time polymerase chain reaction method was performed using SYBRPremix Ex TaqTM II (Tli RNaseH Plus; Takara) and designed primers specific for each gene in an iQ5 thermocycler (BioRad Laboratories) according to the manufacturer's instructions. Results: Our results showed that the expression level of IL‐1 and TNF‐α were significantly higher in the ischemic patients compared to healthy controls ( p  < 0.001, p  < 0.01, respectively); also, we found higher levels of IL‐1 and IL‐27 gene expressions in idiopathic patients compared to healthy controls ( p  < 0.001, p  < 0.001, respectively). There were not any significant differences in IL‐1, IL‐27, and TNF‐α expression levels between ischemic patients and idiopathic ones. Conclusion: Although we would introduce IL‐1, IL‐27, and TNF‐α as effective inflammatory cytokines on myocardial functions in ischemic and idiopathic cardiomyopathy patients, there is not any difference between these two groups in gene expression of three main inflammatory cytokines.